2022
DOI: 10.3389/fvets.2022.819921
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide MPX Can Kill Staphylococcus aureus, Reduce Biofilm Formation, and Effectively Treat Bacterial Skin Infections in Mice

Abstract: Staphylococcus aureus is a common pathogen that can cause pneumonia and a variety of skin diseases. Skin injuries have a high risk of colonization by S. aureus, which increases morbidity and mortality. Due to the emergence of multidrug-resistant strains, antimicrobial peptides are considered to be among the best alternatives to antibiotics due to their unique mechanism of action and other characteristics. MPX is an antibacterial peptide extracted from wasp venom that has antibacterial activity against a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Effective antibiofilm treatment strategies are desperately needed [ 54 ], and there are a plethora of novel strategies and compounds in development to address this pressing issue [ 158 , 159 , 160 ]. Many workers seek to co-opt, enhance, and reinvigorate existing wound-care treatments [ 59 , 161 ], whilst others look to innovate new treatments, such as antimicrobial peptides (AMPs) [ 162 , 163 ], topical antiseptics [ 164 ], nanotechnologies [ 165 , 166 ], or photodynamic therapy [ 167 , 168 ], to target chronic-wound biofilm. Larval therapy is an established and efficacious chronic-wound debridement therapy, achieved through the extracorporeal digestion of devitalized tissue by L. sericata ES.…”
Section: Discussionmentioning
confidence: 99%
“…Effective antibiofilm treatment strategies are desperately needed [ 54 ], and there are a plethora of novel strategies and compounds in development to address this pressing issue [ 158 , 159 , 160 ]. Many workers seek to co-opt, enhance, and reinvigorate existing wound-care treatments [ 59 , 161 ], whilst others look to innovate new treatments, such as antimicrobial peptides (AMPs) [ 162 , 163 ], topical antiseptics [ 164 ], nanotechnologies [ 165 , 166 ], or photodynamic therapy [ 167 , 168 ], to target chronic-wound biofilm. Larval therapy is an established and efficacious chronic-wound debridement therapy, achieved through the extracorporeal digestion of devitalized tissue by L. sericata ES.…”
Section: Discussionmentioning
confidence: 99%
“…Against S. aureus , Yagi et al showed that adipose-derived human MSC conditioned media significantly inhibited S. aureus growth in vitro even without continued adipose-derived human MSC presence, and antimicrobial peptide production, namely LL-37, could be enhanced with the addition of vitamin D. In vivo , Johnson, Webb and Dow demonstrated that MSC therapy also induced antimicrobial peptide production and enhanced antibiotic treatment against a chronic S. aureus biofilm infection in mice [ 512 , 513 , 514 ]. Non-human antimicrobial peptides, such as MPX from wasp venom have also demonstrated efficacy against S. aureus in vitro and in a mouse wound infection model [ 515 ]. The currently known antimicrobial peptides that have exclusively shown antibacterial activity against VISA and VRSA, and their possible mechanisms of action have been reviewed by Hernández-Aristizábal and Ocampo-Ibáñez [ 516 ].…”
Section: Alternative Treatment Options For Vancomycin Resistant Infec...mentioning
confidence: 99%
“…To this end, the effects of the antimicrobial peptide MPX on the gram-positive bacterium S. aureus ATCC 25923, the gramnegative bacteria E. coli ATCC 25922 and Salmonella CVCC 541, and the fungus Candida albicans ATCC 90029 were investigated in this experiment. In addition, previous studies in our laboratory showed that the antimicrobial peptide MPX has a good relieving effect on skin in ammation caused by S. aureus [12]. However, the effect on acute in ammatory injury caused by S. aureus is still unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Preliminary studies in our laboratory have shown that MPX has good bactericidal potential [11,12]. However, the broad-spectrum antimicrobial properties of MPX are still unknown.…”
Section: Introductionmentioning
confidence: 99%